12x-6x-86=82

Simple and best practice solution for 12x-6x-86=82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x-6x-86=82 equation:


Simplifying
12x + -6x + -86 = 82

Reorder the terms:
-86 + 12x + -6x = 82

Combine like terms: 12x + -6x = 6x
-86 + 6x = 82

Solving
-86 + 6x = 82

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '86' to each side of the equation.
-86 + 86 + 6x = 82 + 86

Combine like terms: -86 + 86 = 0
0 + 6x = 82 + 86
6x = 82 + 86

Combine like terms: 82 + 86 = 168
6x = 168

Divide each side by '6'.
x = 28

Simplifying
x = 28

See similar equations:

| 6x-8x-22=24 | | f(x)=4x^2-4x-8 | | 58-5x+x=62 | | 15y=-10x+40 | | 2w-4=a | | 4x=8y-16 | | 70-7x-2x=65 | | X^2-mx+9=0 | | -x+5x+6=18x+36 | | 24+6i=4x-3yi | | 2x+7=12x+5 | | 4x+3=27-8x | | 2y+6=-20 | | 12x-30+4x+2= | | 8(x+7)=15x-56 | | 2x-2(2)=2 | | 231-y=118 | | 3x-11+2x+5=180 | | 2(-4)-2y=2 | | 276=219-w | | a=2w-4 | | 432t*t-72*t+3=0 | | y+6=5(x-2) | | -u+271=198 | | 0.18x+0.9(x-3)=0.01(5x-5) | | 432*t*t-72*t+3=0 | | 36-2y=7y | | 2t^2-75t=-3t^3+50 | | 94c+74=4c | | 7x-9=11x+37 | | 6y=25+y | | 17=4x+2 |

Equations solver categories